Total war in Tudor England - Gunn, S (Immediate Media, 2018)
One day in the early 1520s John Byrcham, Robert Saumon, Bartholomew Storme and Robert Wyndell of Whitby went out fishing. As they headed back to port with their catch they were intercepted by a French warship and taken prisoner. They negotiated a ransom of £22 6s 8d to free themselves, their ship and their fish, and Byrcham went into Whitby and on to Bridlington to get the money from the ship’s owners, a widow called Elizabeth Dodys and William Browneflete, head of the town’s rich Augustinian Priory. Byrcham returned and paid off the French, who let the ship go. The crew’s relief did not last long, as they were captured by Scottish raiders before they could get back to harbour. The Whitby fishermen’s story belongs to the hidden history of Henry VIII’s wars. Henry’s posturing in European politics is well enough known, but the full impact of his wars on the people he ruled tends to be overlooked. Our attention is irresistibly drawn elsewhere: to his attacks on the church, the bloody politics of his court, or the social strains of enclosure, inflation and popular revolt. Yet Henry’s people spent something like half his reign at war, against the French, the Scots, the Gaelic lords of Ireland, rebels at home, or even England’s traditional allies in the Low Countries.